Antioxidant activity of selenenamide-based mimic as a function of the aromatic thiols nucleophilicity, a DFT-SAPE model. (August 2018) - Kheirabadi, Ramesh; Izadyar, Mohammad
Graphical abstract: Catalytic Activity of Glutathione Peroxidase Mimic. Highlights: New generation of amide-based organo-selenium enzyme mimic was theoretically investigated. DFT and SAPE methods were applied to model the catalytic cycle of the enzyme mimic. The effect of various aromatic thiols on the kinetic and thermodynamic of catalytic cycle was analyzed. Turnover frequency calculations confirmed the rate determining step of the catalytic cycle. Electron-donating substituent effects were analyzed by using the NBO and GEDT calculations. Abstract: The mechanism of action of the selenenamide 1 as a mimic of the glutathione peroxidase (GPx) was investigated by the density functional theory. The solvent-assisted proton exchange procedure was applied to model the catalytic behavior and antioxidant activity of this mimic. To have an insight into the charge transfer effect, different aromatic thiols, including electron donating substituents on the phenyl ring were considered. The catalytic behavior of the selenenamide was modeled in a four-step mechanism, described by the oxidation of the mimic, the reduction of the obtained product, selenoxide, the reduction of the selenenylsulfide and dehydration of selenenic acid. On the basis of the activation parameters, the final step of the proposed mechanism is the rate determining states of the catalytic cycle. Turnover frequency (TOF) analysis showed that the electron donating groups at the para-position of the phenyl ring of the PhSH do not affect the catalytic activity of the selenenamide in contrast to p-methyl thiophenol which indicates the highest nucleophilicity. The evaluation of the electronic contribution of the various donating groups on the phenyl ring of the aromatic thiols shows that the antioxidant activity of the selenenamide sufficiently increases in the presence of the electron-donating substitutions. Finally, the charge transfer process at the rate-determining state was investigated based on the natural bond orbital analysis.